2022
DOI: 10.1101/2022.09.01.506150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of conserved skeletal enhancers associated with craniosynostosis risk genes

Abstract: Craniosynostosis (CS) is a common congenital defect affecting more than 1/2000 infants. Infants with CS have a premature fusion of one or multiple cranial sutures resulting in restricted brain expansion. Single gene mutations account for 15-20% of cases, largely as part of a syndrome, but the majority are nonsyndromic with complex underlying genetics. Two noncoding genomic regions contributing to CS risk were previously identified by GWAS, one near BMP2 and one within BBS9. We hypothesized that the region with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In addition, in the presence of twisted gastrulation, full-length BMPER inhibits BMP-signaling in C2C12 cells (52). The results of a previous study have also demonstrated that BMPER exerts positive and negative effects on BMP activity, and these effects are context-dependent (53).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, in the presence of twisted gastrulation, full-length BMPER inhibits BMP-signaling in C2C12 cells (52). The results of a previous study have also demonstrated that BMPER exerts positive and negative effects on BMP activity, and these effects are context-dependent (53).…”
Section: Discussionmentioning
confidence: 83%
“…Although murine studies have been crucial for understanding the biology of cranial sutures and how suture closure is regulated, zebrafish are emerging as a model organism for understanding this process; zebrafish have been used to model Saethre-Chotzen syndrome (caused by mutations in TWIST1 and TCF12 ) and craniosynostosis caused by alterations to retinoic acid synthesis ( Laue et al, 2011 ; Teng et al, 2018 ). A recently published zebrafish study identified putative enhancers of bmp2 and bmper (a regulator of BMP signaling) that drive reporter gene expression in the osteogenic fronts of transgenic zebrafish calvaria, suggesting that the function of BMP signaling in cranial development and suture homeostasis is conserved in zebrafish ( He et al, 2023 ).…”
Section: Zebrafish Studies Of Tgf-β Signaling and Craniofacial Develo...mentioning
confidence: 99%
“…Studies have shown that zebrafish are a tractable model for studying suture biology and craniosynostosis, and the prospect of using zebrafish to study the suture biology and the pathogenesis of craniosynostosis is exciting ( Laue et al, 2011 ; Teng et al, 2018 ). With respect to BMP signaling, a recent zebrafish study identified that GWAS variants associated with BMP2 lie in putative enhancer regions for BMP2 and BMPER, and that these enhancers likely drive the expression of these genes in the osteogenic fronts of the frontal bones, further implicating BMP signaling in suture homeostasis and craniosynostosis ( Justice et al, 2012 ; He et al, 2023 ). Furthermore, yeast 2 hybrid assays indicated that the GWAS variants in these enhancers abrogate transcription factor binding ability, further suggesting that altered BMP signaling contributes to the pathogenesis of craniosynostosis ( He et al, 2023 ).…”
Section: Human Craniofacial Diseases and Tgf-β Signalingmentioning
confidence: 99%
See 2 more Smart Citations